Outcome of subvastus approach in elderly nonobese patients undergoing bilateral simultaneous total knee arthroplasty: A randomized controlled study - Jain, Sanjeev (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Subvastus approach in total knee arthroplasty (TKA) spares the quadriceps and may assist in faster rehabilitation. The present randomised controlled study was conducted to determine if the subvastus approach results in early recovery, faster mobilization, shorter hospital stay, and improved function. MATERIALS AND METHODS: 100 patients undergoing simultaneous bilateral TKA were randomized into two groups: subvastus group and medial parapatellar group. The patients were assessed clinically using VAS, time to straight leg raise, ability to stand with walker, ability to use a commode chair, ability to climb stairs, flexion at discharge, and day of discharge. Perioperative blood loss and duration of surgery were also compared. The patient were kept on same pain management and physiotherapy protocol. The evaluation was done at day 0,1,3 and at discharge. Statistical analyses tested the null hypotheses of no differences in patients treated with either group at 95% significance level (P < 0.05). RESULTS: The VAS score was significantly lower in subvastus group on day 1 and day 3. Also mean hospital stay was 2.04 days less in subvastus group. Patients with subvastus approach were able to perform straight leg raising 0.44 days earlier. Though time to stand with walker was same for both groups, the ability to use commode chair, and climb stairs was significantly early (P < 0.05) in the subvastus group. The average flexion at the time of discharge in subvastus and parapatellar group were 100.8 and 96.8°, respectively. The mean perioperative blood loss in subvastus group and parapatellar group were 343 ml and 372 ml, respectively. Average surgical time required for subvastus approach and parapatellar approach were 108.5 and 94.3 min, respectively. CONCLUSIONS: Subvastus approach produce appreciably less pain and faster mobilization due to lesser insult to quadriceps, thus assisting in early rehabilitation, shorter hospital stay, less expenditure, and more patient satisfaction.